Evaluation of Academic Staff Job Satisfaction at Malaysian Universities in the Context of Herzberg’s Motivation-Hygiene Theory - Mehrad, Aida (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2020)
Most academic staff don’t know what exactly makes them satisfy or dissatisfy at university and based on which effective factors they can improve and increase the level of their outcomes. Dissatisfaction occurred amongst academic staff when they don’t receive any basic motivational factors, versa job satisfaction happened when they obtained at least the fundamental facilities and considered via workplace (managers, leaders, and supervisors). There are numerous and effective factors that change attitudes and feelings of academic staff toward the job, likewise, change level of their outcomes; furthermore, recognizing these effective factors that rise level of job satisfaction among these group of staff; similarly, analyzing this factor as one of the important organizational factors in the context of Herzberg’s Motivation-Hygiene Theory determined as main objective of this literature review. Overall, in this research endeavors to finding brilliant points and motivational factors that influence job satisfaction and clarifies them in an educational situation such as the university.